The Legal Standing and Regulation of Legal Counsel for Members of the Indonesian National Police - Rasyid, Rahmat Eka Putra; W. Badu, Lisnawaty; Apripari, Apripari (Universitas Negeri Gorontalo, 2025)
This article aims to analyze the regulation of legal counsel within the profession of the Indonesian National Police (Polri), as well as to examine the legal basis that enables Polri to provide legal assistance. This study adopts a normative legal research method, utilizing statutory and conceptual approaches. Legal materials were collected through document studies and analyzed prescriptively. The findings indicate that the role of legal counsel in Indonesia is generally governed by Law Number 18 of 2003 concerning Advocates and Article 1 paragraph (13) of the Indonesian Criminal Procedure Code (KUHAP). However, Polri also has its own internal regulations regarding legal counsel, particularly Regulation of the Chief of the Indonesian National Police Number 2 of 2017 on the Procedures for Providing Legal Assistance by Polri, especially Article 1 paragraph (6) and Article 5 paragraph (2). This regulatory framework raises juridical issues as it is not fully aligned with the provisions of the Advocates Law, particularly Article 3 paragraph (1) letter c, which stipulates that only licensed advocates have the right to provide legal services. Therefore, a legal review of conflicting norms is necessary to ensure legal certainty and to prevent overlapping authority between the advocate profession and legal counsel within Polri.